Efficacy of Muscle Energy Technique Versus Instrument- Assisted Soft Tissue Mobilization on Postnatal Low Back Pain - Marwa A Aziz; Hanafy, Hala M; Awad, Mohamed A.; Salem, Hossam Eldin H (International Journal of Psychosocial Rehabilitation, 2020)
Low back pain (LBP) is more common in the postpartum period. In fact, up to 75% of women who suffer from pregnancy-related back pain may continue to have pain after giving birth. The purpose of this study is to compare effectiveness of muscle energy technique versus instrument- assisted soft tissue mobilization on postnatal low back pain. 40postnatal women participated in this study. They complained from low back pain. They were selected from Said Galal University Hospital in Cairo, Al Azhar University. Their ages ranged from 25 to 35 years old. Their body mass index was not exceeding 30 kg/m2. All of them were after normal vaginal delivery by 6 weeks. Patients with radiculopathy, previous low back surgery, spondylolisthesis and chronic low back pain were excluded from the study. They were divided randomly into two equal groups (A& B). Group A treated by instrument assisted soft tissue mobilization (IASTM) two times/ week for six weeks. Group B treated by muscle energy technique (MET) two times /week for six weeks. All patients in both groups were evaluated pre- and post-treatment with Visual analogue scale (VAS) was used to measure pain intensity and Modified Schober’s test was used to assess ROM for both groups A and B before and after treatment. Statistical analysis using pre and post treatment design indicated that, within groups There was a statistically highly significant decrease (P<0.001) in VAS and a statistically highly significant increase (P<0.001) in lumbar spine ROM in both groups A and B post treatment. Between groups the obtained results showed that there was no statistical significant difference pre treatment, but post treatment there was a statistically highly significant difference in low back pain intensity (more decrease in group A) and lumbar spine ROM (more increase in group A). Instrument assisted soft tissue mobilization technique is more effective than muscle energy technique in reducing postnatal low back pain intensity and improving lumbar spine ROM.